Spiriti - Ebisuno, Yukai; Mantegazza, Raffaella (Italy, 2012)
There is a place between the mountains of Honduras where rituals and prayers mark the passage of time. An elderly woman walks barefoot in the mountain. A man dies accompanied by an angel. Spirits are the voice of ancestors and the courage of a small indigenous community that would rather take care of the Earth than sell it.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films